Bioprocessing of waste biomass for sustainable product development and minimizing environmental impact. (February 2021) - Usmani, Zeba; Sharma, Minaxi; Awasthi, Abhishek Kumar; Sivakumar, Nallusamy; Lukk, Tiit; Pecoraro, Lorenzo; Thakur, Vijay Kumar; Roberts, Dave; Newbold, John; Gupta, Vijai Kumar
Graphical abstract: Highlights: Biomass waste is an important resource towards development of sustainable bioproducts. Bacteria, fungi and crude enzymes can convert biomass waste into value-added products. Lifecycle assessment of bioprocessing can help optimize production and reduce waste. Techno-economic analysis of bioprocessing can help industrialize biomass waste treatment. Abstract: Growing concerns around the generation of biomass waste have triggered conversation around sustainable utilization of these seemingly waste materials as feedstock towards energy generation and production of chemicals and other value-added products. Thus, biotechniques such as utilization of microbes and enzymes derived thereof have become important avenues for green pretreatment and conversion of biomass wastes. Although the products of these bioconversions are greener at an overall level, their consumption and utilization still impact the environment. Hence it is important to understand the overall impact from cradle to grave through lifecycle assessment (LCA) techniques and find avenues of process optimization and better utilization of all the materials and products involved. Another factor to consider is overall cost optimization to make the process economically feasible, profitable and increase industrial adoption. This review brings forward these critical aspects to provide better understanding for the advancement of bioeconomy.